Repurposing drugs as uS12 ribosomal protein inhibitors to overcome UTI resistance in MDR Pseudomonas strains: In silico and in vitro study - Sharma P.; Tripathi A.D.; Kalra A.; Chouhan B. (My University, 2025)
Multidrug-resistant (MDR) strains of Pseudomonas spp.in UTI (urinary tract infection) present a substantial worldwide health concern, requiring the development of novel approaches to identify alternative therapeutic interventions. This investigation utilizes a computational drug repurposing approach utilizing in silico docking studies to investigate the potential repurposing of 63 currently available non-antibiotic drugs and a control substance, streptomycin, against the uS12 ribosomal protein. The uS12 protein serves as a potential target for inhibiting translation in bacteria, potentially contributing to the mechanism by which streptomycin exerts control. The objective was to identify potential candidates that possess the capability to inhibit essential drug-resistant targets, specifically uS12. Based on our research, the observed binding energy of the control was determined to be-6 kilocalories per mole. Additionally, out of the total 63 samples tested, only 12 were found to exhibit binding energy in the range of-5.8 kilocalories per mole and above. The computational analysis of the pharmacokinetics of the 12 drugs reveals a diverse range of outcomes that support both oral and intravenous administration routes for the gathered drugs. The results of the in vitro minimum inhibitory concentration (MIC) analysis, Rhamnolipid, and Phycocyanin inhibition assays conducted on various strains of Pseudomonas spp. indicated that amlodipine, hydroxychloroquine, 5FU, Indomethacin, ascorbic acid, and calaptin exhibited higher potency compared to other drugs. The MIC values for these drugs ranged from 8.60 to 116.93 µg/mL. The results of this study show potential for expediting drug development using in silico repurposing methods, as well as addressing the urgent issue of antibiotic resistance in Urinary tract infections. © 2024, National Institute of Science Communication and Policy Research. All rights reserved.